2021
DOI: 10.3389/fonc.2021.757323
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Energy: Breaking Down the Diverse Metabolic Features of Lung Cancers

Abstract: Metabolic reprogramming is a hallmark of cancer initiation, progression, and relapse. From the initial observation that cancer cells preferentially ferment glucose to lactate, termed the Warburg effect, to emerging evidence indicating that metabolic heterogeneity and mitochondrial metabolism are also important for tumor growth, the complex mechanisms driving cancer metabolism remain vastly unknown. These unique shifts in metabolism must be further investigated in order to identify unique therapeutic targets fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 150 publications
0
7
0
Order By: Relevance
“…We identified 11 commonly shared glutamine metabolismrelated lncRNAs in three different LUAD data cohorts using glutamine metabolism scores and ssGSEA. Several previous studies have highlighted the metabolic heterogeneity in lung tumors [30], suggesting that LUAD may have different metabolic phenotypes. To investigate the metabolic phenotypes, we classified the LUAD samples into three glutamine metabolic subtypes based on the 11 glutamine metabolismassociated lncRNAs.…”
Section: Computational and Mathematical Methods In Medicinementioning
confidence: 99%
“…We identified 11 commonly shared glutamine metabolismrelated lncRNAs in three different LUAD data cohorts using glutamine metabolism scores and ssGSEA. Several previous studies have highlighted the metabolic heterogeneity in lung tumors [30], suggesting that LUAD may have different metabolic phenotypes. To investigate the metabolic phenotypes, we classified the LUAD samples into three glutamine metabolic subtypes based on the 11 glutamine metabolismassociated lncRNAs.…”
Section: Computational and Mathematical Methods In Medicinementioning
confidence: 99%
“…Metabolic reprogramming is a key hallmark of NSCLC and is critical for the sustained cancer cell proliferation [35][36][37]. Like other malignancies, altered metabolic features in NSCLC can provide enough nutrients for cancer growth [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic reprogramming is a key hallmark of NSCLC and is critical for the sustained cancer cell proliferation [35][36][37]. Like other malignancies, altered metabolic features in NSCLC can provide enough nutrients for cancer growth [35][36][37]. Ji et al, have demonstrated that SLC7A11 is a key regulator of metabolic reprogramming during NSCLC tumorigenesis and progression and is essential for glucose metabolism, glutamine dependency, and intracellular GSH/GSSG redox balance in NSCLC cells [38].…”
Section: Discussionmentioning
confidence: 99%
“…The increased dependence of lung cancer cells on glucose uptake and upregulated glycolysis provides an interesting biochemical basis for developing systemic anticancer treatments that preferentially target cancer cells by pharmacological inhibition of glycolysis. Glucose transporters and glycolytic enzymes are overexpressed in lung cancer, and inhibition of these targets provides an attractive avenue for developing new anticancer treatments [ 85 ]. Several inhibitors of glycolytic enzymes and transporters are in preclinical development, yet none of them have approved status [ 4 ].…”
Section: Quantitative Nmr Metabolomicsmentioning
confidence: 99%